No improvement in maximum jumping height in experienced and less experienced jumpers following a single session of transabdominal, transcutaneous spinal anodal direct current stimulation - Beszterda, Izabela; Grześkowiak, Marcin; Wieczorek, Andrzej; Łochyński, Dawid; Jadczak, Łukasz (Frontiers in Physiology, 2026)
IntroductionConflicting findings have been reported about effects of transcutaneous spinal direct current stimulation (tsDCS) on jumping performance, as transabdominal tsDCS was shown to enhance maximum jumping height while spine-shoulder did not. The aim of the study was to evaluate effects of anodal transabdominal tsDCS in prone lying on jumping height in less experienced (LEJ) and experienced (EJ) jumpers.MethodsParticipants from LEJ (physical education students, 13 men and 10 women) and EJ (volleyball players, 13 men and 10 women) were subjected to a single 15-min session of anodal transabdominal tsDCS. Maximum vertical jumping height was measured during two sets of maximum squat jumps (SJs) and counter movement jumps (CMJs) performed in randomized order immediately, 30- and 60-min post stimulation. One set was composed of 3 jumps. There was 3-min break between the sets and 1 min rest between the jumps.ResultsTwo-way analysis of variance did not show the effect of interaction between the stimulation and time on jumping height during SJ (F2,44 = 1.629; p = 0.208) and CMJ (F2,44 = 1.304; p = 0.282) in EJ, as well as during SJ (F2,44 = 1.346; p = 0.271) and CMJ (F2,44 = 0.228; p = 0.747) in LEJ.ConclusionTsDCS does not improve jump height in either squat or countermovement jumps in recreationally active and professional volleyball players. The results question the use of single session of transabdominal tsDCS in recreational or sports training to improve jumping performance.